Subjectivity in the valuation : Case study on the Finnish biotechnology industry - Paju, Ilkka (My University, 2012)
The thesis combines valuation and behavioral economics literature, which is not common among the Finnish management accounting research. Furthermore, the valuation is studied in biotechnology context and those type of studies are rather rare as well. The thesis studies the valuation in the Finnish biotechnology industry. The concepts of behavioral finance are employed in the empirical part of the study to explore decision-makers’ behavior in valuation processes. The main interest of this study is to explore how subjectivity of a decision-maker affects the valuation in the biotechnology industry. The valuation is studied from two perspectives. First, what is the best valuation model for biotechnology companies suggested by the valuation literature? Second, how the valuation in biotechnology industry is done in practice and how the decision-makers subjectivity affects the valuation? The literature review aims at seeking the best valuation model. The real options were found to be the most suitable valuation model for biotechnology companies, especially in the early stages of product development. The real option’s ability to take the value of the inherent options into account results in theoretically most correct valuations. The only disadvantage is the model’s complexity when compared to other models, such as discounted cash flow models. The empirical part of the study consists of a case study, which examines the valuation practices of the Finnish biotechnology companies. When it comes to the valuation models used in practice, it was found that the companies were using rather simple valuation models, which was due to two reasons. First, the interviewees did not believe in the valuation models and second, they were familiar neither with the most sophisticated models nor with all the theoretical aspects of the models they were using. The material for the study was collected with theme interviews. Four CEO’s of highly successful Finnish biotechnology companies. Strong signs of the decision-makers’ subjectivity in valuation were observed. Most obvious were the signs of framing. Furthermore, herding, excessive optimism, and overconfidence were present. All the behavioral concepts observed most likely have a severe effect on the valuation. As a result, the valuation can easily become overly optimistic, which leads to overvalued investments and to continuation of already unprofitable projects. Framing had the strongest evidence. If the product being valued is framed successfully, the risk of overvaluation is high, thus a strong belief can justify almost any value.